Determination of the standard leaf for nutritional diagnosis of assai palm plants - Viégas, Ismael de Jesus Matos; Muller, Antônio Agostinho; Costa, Milton Garcia [UNESP]; Ferreira, Eric Victor de Oliveira; Pinheiro, Daniel Pereira; Campos, Pedro Silvestre da Silva (FapUNIFESP (SciELO), 2022)
Assai palm is the main palm tree grown in the Brazilian Amazon. Nutritional diagnosis has become an essential tool in management of the crop. The aim of this study was to determine the standard leaf for nutritional diagnosis of the assai palm tree through evaluation of leaf nutrient content and use of two methods of statistical analyses: traditional (univariate) and multivariate. The study was conducted in the municipality of Belém, with eight treatments: the phyllotaxic positions of the leaves (number 2 to 9), in a completely randomized design. The leaf concentration of nutrients (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn) was determined for performing descriptive analyses, analyses of variance, correlation analysis, and principal component analysis (PCA). Young leaves had greater concentrations of N, P, K, Mg, S, Cu, and Zn, whereas in the older leaves, there were greater concentrations of Ca, B, Fe, and Mn. The leaves that exhibited less variation in nutrient concentrations were from 2 to 5. PCA analysis indicated interaction of positive loads of N-P and Cu-Mg and interaction of negative loads of Ca-Mn. The index of nutrient distribution indicated leaf number 5 as having the lowest factor loading value. Thus, leaf number 5 is most recommended for nutritional diagnosis of assai palm plants through sampling of 25 plants.
Determinação da folha padrão para diagnóstico nutricional do Açaizeiro
Keywords: diagnostic leaf; Euterpe oleracea Mart; leaf sampling; nutritional state; plant nutrition